2021
DOI: 10.1186/s13020-021-00512-4
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral alternations of the female offspring born to polycystic ovary syndrome model rats administered by Chinese herbal medicine

Abstract: Background Chinese herbal medicine (CHM) has significant effects that improve the reproductive functions of patients with polycystic ovary syndrome (PCOS). However, the intergenerational effects of CHM on offspring and the underlying mechanism of CHM remain unclear. This study aimed to explore the effects and the underlying mechanism of CHM, specifically the Bu-Shen-Tian-Jing formula (BSTJF), on model rats with polycystic ovary syndrome (PCOS) and the neurobehavioral alterations of female offsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Concerning neurobehavioral phenotypes, maternal PCOS has been reported to respectively increase the odds of offspring attention-de cit/hyperactivity disorder (ADHD) and autism spectrum disorders (ASD) by 42% and 59% [13][14][15][16]. Consistently, the previous work of the author's group has suggested a different pattern of brain metrics in PCOS offspring in utero [17], and alterations of neurobehavioral phenotypes in female offspring of both women with PCOS[18] and PCOS model rats [19] which might involve learning and memory. Hence, further study is needed to con rm the role of maternal PCOS in early offspring neurodevelopment for both boys and girls.…”
Section: Introductionmentioning
confidence: 54%
“…Concerning neurobehavioral phenotypes, maternal PCOS has been reported to respectively increase the odds of offspring attention-de cit/hyperactivity disorder (ADHD) and autism spectrum disorders (ASD) by 42% and 59% [13][14][15][16]. Consistently, the previous work of the author's group has suggested a different pattern of brain metrics in PCOS offspring in utero [17], and alterations of neurobehavioral phenotypes in female offspring of both women with PCOS[18] and PCOS model rats [19] which might involve learning and memory. Hence, further study is needed to con rm the role of maternal PCOS in early offspring neurodevelopment for both boys and girls.…”
Section: Introductionmentioning
confidence: 54%
“…Our previous studies have demonstrated that BSTJF1 had positive effects in improving ovarian function (Zhang et al. 2021 ; Pan et al. 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Animal studies have shown that BSTJF1 effectively improves ovarian follicle development in PCOS rats and reduces swollen mitochondria, ruptured mitochondrial cristae, and rough endoplasmic reticulum in progeny born to the BSTJF1 group (Zhang et al. 2021 ). However, the pharmacological effects of BSTJF2 have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the complicated and uncertain COVID-19 pandemic, the patient-centered outcome measures could be recommended to be designed and used to assess the effects of integrative medicine on the female reproductive health relevant to the virus. Integrative medicine like Chinese herbal medicine 11 , acupoint hot compress 12 makes great promises in addressing these issues, because the integrative medicine not only has the ability of antivirus, anti-inflammation, immune regulation and organ protection from integrative medicine in management of COVID-19 13 but also can be applied for physical and mental relaxation, anxiety relief and sleep assistance to improve female reproductive health during the COVID-19 pandemic ( Fig. 1 ).…”
mentioning
confidence: 99%